(untitled) (Revista Contexto & Saúde, 2022)
Objective: identify and characterize the trends of Brazilian theses and dissertations about safety in the transfusion act Method: narrative review of the literature, carried out in February 2020, based on the productions available in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel, using the keyword “transfusion act”. Studies that included strategies to improve safety in the transfusion act were included. Results: the corpus of this review consisted of seven studies. It was observed as a tendency dissertations developed in public institutions, in the southeast region, with a predominant year of defense in 2019 and research involving nursing professionals. As for the object of study, it was possible to list two categories: knowledge of health professionals to work in blood therapy procedures and use and/or development of tools for safety in the transfusion act. Conclusion: the professionals’ lack of knowledge about some stages of transfusion procedures constitutes a threat to patient safety. The use of educational tools and checklists for all stages of the procedure is essential for them to be developed with maximum security.